APPLICATION OF RECIRCULATION AQUACULTURE SYSTEM ON NURSERY PHASE OF THE GOURAMI (Osphronemus gouramy Lac.) - (NIM 20605321), HERNAWATI
The gourami (Osphronemus gouramy Lac.) is one of freshwater fishery commodities that have high economic value. There are several problems related to its culture such as high mortality level of 50-70% during larviculture and nursery phase beside its slowly growth rate. It’s not surprising that under these conditions, gourami yield production is low and unpredictable. Recently, improvement of the culture performance have been focused on diseases control, optimization of feeding regime, and better water quality management. This research was aimed to improve productivity by application the recirculation system with submerged bed biofilter and trickling filter that enable the culture system maintaining better and more stable water quality during nursery phase. In this study, the use of recirculation system equiped with submerged bed biofilter and trickling filter were compared with the control, static system. The recirculation system equiped with submerged bed biofilter consisted of three main devices : (1) culture tank, (2) settling tank, and (3) biofilter; and the recirculation system equiped with trickling filter consisted of two main devices : (1) culture tank and (2) biofilter. For all experiments, a 50 x 35 x 25 cm3 rectangular tank was used and filled with 40 liter of freshwater. The temperature culture was maintained stable at 27 + 10C by mean of submerged water heater and the culture water was aerated constantly by using aeration system. The 4 month old of gourami with initial mean body weight of 9 + 0,23 g and initial mean body length of 7 + 0,14 cm were used. The fish stocking density was 15 individuals/culture tank and for the feeding management, total commercial feed of 3% from the total fish body weight was delivered by following 2x1 feeding frequency. The culture system was performed during 30 days culture period and trial was run by using three replicates per treatment and repeated by time. Several key parameter such as biological parameter (mean weight, total length and survival rate) and water quality (DO, temperature, pH, NH4+, NO2- and NO3-) were measured during the study. Based on the results, the gourami cultured in the recirculation system with trickling filter had highest weight of 15,09 + 0,04 g, body length of 9,35 + 0,25 cm, growth rate of 0,24 + 0,01 g/day, survival rate of 82,2% and biomass of 186,06 + 0,32 g, followed by the recirculation system with submerged bed filter (weight of 14,67 + 0,22 g, body length of 9,30 + 0,25 cm, growth rate of 0,23 + 0,03 g/day, survival rate of 80% and biomass of 176,04 + 6,45 g), and the lowest weight of 13,13 + 0,10 g, body length of 9,10 + 0,13 cm, growth rate of 0,17 + 0,01 g/day, survival rate of 44,47% and biomass of 87,58 + 7,37 g were obtained in the static culture. All of the parameters measured in the recirculation system with trickling filter were not significantly different (p>0,05) compared to recirculation system with submerged bed filter. However, all parameters obtained in both recirculation system were significantly different (p<0,05) compared to the static system except for weight and body length. In term of water quality, the use of recirculation system contributed to the lower and more stable NH4+ and NO2- level compared to the static system. Based on the results, it could be concluded that the application of recirculation system could maintain a better water quality during nursery phase of gourami (Osphronemus gourami Lac.) and enable the culture system increase its productivity.